OPTIMIZING LEGAL REGULATIONS FOR THE PROTECTION OF CYBERSTALKING VICTIMS IN INDONESIA - Roberto, Rafhael; Azzahra, Balqis Tsabitah; Diksy, Khoirunnisa Putri; Ramdhani, Nadia Marsya; Winanti, Atik (Journal Social Sciences and Humanioran Review, 2025)
Cyberstalking involves stalking, monitoring, or harassing someone continuously through digital media, which can threaten an individual's privacy and cause psychological distress to the victim, including anxiety, trauma, and insecurity. Although there are laws regulating cyberstalking, legal protection for victims of cyberstalking is still inadequate due to limitations in handling cyberstalking cases. This study examines legal protections for victims of cyberstalking in Indonesia and identifies efforts to optimize cyberstalking regulations in the country. This study uses a normative legal approach (doctrinal research) with a statutory approach and a conceptual approach. The results of this analysis show that legal protection for victims of cyberstalking in Indonesia still faces challenges. Although there are regulations to handle cyberstalking cases, law enforcement remains ineffective and incomplete, and there are no specific regulations addressing cyberstalking. Additionally, legal loopholes indicate legal weaknesses in the regulation of cyberstalking in Indonesia. Therefore, it is necessary to establish a specific law that specifically regulates cyberstalking and revise existing regulations to strengthen the legal framework governing cyberstalking. Furthermore, it's important to raise awareness about cyberstalking and strengthen technological infrastructure in digital investigations so that the law can be enforced effectively and comprehensively, thereby protecting victims of cyberstalking in Indonesia.